Fate and removal of Ciprofloxacin in an anaerobic membrane bioreactor (AnMBR). (October 2019) - Do, Mai T.; Stuckey, David C.
Highlights: Tested removal of 0.5–4.7 mg/L Ciprofloxacin (CIP) in anaerobic membrane bioreactor. 50–76% CIP removed with 0.5–1.5 mg CIP/L feed; at 4.7 mg/L removal efficiency <20%. Biodegradation main method for removing CIP, while adsorption only a small fraction. CIP was biodegraded to intermediate compounds detected using LC–MS/MS and GC–MS. Work showed AnMBR effectiveness in removing CIP at low concentrations of <1.5 mg/L. Abstract: This study examined the removal of varying concentrations of the antibiotic Ciprofloxacin (CIP) over the long-term (120 days) in an anaerobic membrane bioreactor (AnMBR). The results showed that 50–76% CIP was removed with 0.5–1.5 mg CIP/L in the feed, although at 4.7 mg/L its removal efficiency decreased to <20%. It was found that biological degradation was the main mechanism for removing CIP, while adsorption onto the sludge only contributed a small fraction, and an even smaller fraction was due to the waste sludge discharged. CIP was biodegraded to some degree in the AnMBR, with some intermediate compounds detected using LC–MS/MS and GC–MS. This work showed the effectiveness of an AnMBR in removing CIP at low concentrations of <1.5 mg/L, and hence may be an effective treatment for removing other antibiotics from wastewater.